2015
DOI: 10.1097/md.0000000000000880
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Analgesia With Bupivacaine and Fentanyl Versus Ropivacaine and Fentanyl for Pain Relief in Labor

Abstract: The aim of this study was to compare the efficacy and safety of the combinational use of bupivacaine and fentanyl versus ropivacaine and fentanyl in epidural analgesia for labor.Multiple electronic databases were searched by using appropriate MeSH terms, and keywords for original research papers published before October 2014. Meta-analyses were based on mean differences between the groups as well as odds ratios. Statistical heterogeneity was tested by I2 index.Fifteen randomized controlled trials, recruiting 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…5 Similar to our study, Guo S et al, in their metaanalysis also found that Analgesia with ropivacaine in combination with fentanyl is associated with lower incidence of motor blocks in comparison with bupivacaine and fentanyl at a similar ratio (0.1%: 0.0002%). 19 Meister GC et al, also observed similar results to our study. In contrast, Halpern SH et al, observed that there was no significant difference between the two drugs in the mode of delivery, maternal satisfaction, or neonatal outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5 Similar to our study, Guo S et al, in their metaanalysis also found that Analgesia with ropivacaine in combination with fentanyl is associated with lower incidence of motor blocks in comparison with bupivacaine and fentanyl at a similar ratio (0.1%: 0.0002%). 19 Meister GC et al, also observed similar results to our study. In contrast, Halpern SH et al, observed that there was no significant difference between the two drugs in the mode of delivery, maternal satisfaction, or neonatal outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…18 Most studies and reviews have found epidural Ropivacaine and Bupivacaine, with or without opioids, to be similar when compared at equal concentrations ranging from 0.125 to 0.25% for maintenance of labor analgesia and this may not be consistent with different concentrations and their analgesic potency must also be considered. 5,15,16,[19][20][21] In this study, Bupivacaine group needed a higher number of top-ups compared to Ropivacaine group. Only 28% in the Ropivacaine group needed 3 top ups or more compared to 76% in Bupivacaine group.…”
Section: Discussionmentioning
confidence: 66%
“…Previously, significantly lower incidence of motor blocks is reported in parturient mothers who received epidural analgesia with ropivacaine and fentanyl (18.4%) than in women who received bupivacaine and fentanyl (32.8%) for labor epidural analgesia . This may be due to the low lipophilic characteristics of ropivacaine which make it resistant to a rapid penetrance in the myelinated nerve fibers .…”
Section: Discussionmentioning
confidence: 96%
“…7 Asik et al concluded that epidural bupivacaine 0.2% and ropivacaine 0.2% combined with fentanyl produced equivalent analgesia for pain relief during labor and delivery. 8 It is concluded that ropivacaine 0.2% combined with fentanyl 2 microg mL (-1) provided effective analgesia with significantly less motor block and need for an instrumental delivery than a bupivacaine/fentanyl combination at the same concentrations during labor and delivery.…”
Section: Discussionmentioning
confidence: 99%